A Comparative Study of Atmospheric Boundary Layer Characteristics Over New Delhi During 2001–2010 (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Atmospheric Boundary Layer (ABL) plays a crucial role in regulating weather, climate, and air quality, particularly over urban regions. This study investigates the temporal and seasonal variability of Atmospheric Boundary Layer characteristics over New Delhi during the period 2001–2010 using ERA-5 reanalysis data. Key parameters such as Boundary Layer Height (BLH), surface temperature, and wind speed are analysed on annual and seasonal scales. The results reveal pronounced seasonal variations, with maximum BLH observed during the pre-monsoon season and minimum values during winter. Inter-annual variability highlights the influence of surface heating and urbanization on boundary layer development. The findings provide insight into urban boundary layer dynamics and their implications for air pollution dispersion over New Delhi.